Democratic Governance Of Religion The Abdul Karim Soroush Model - Hakiki, Kiki Muhamad; Rohmatika, Ratu Vina; Muttaqien, Zaenal (Universitas Islam Negeri Raden Intan Lampung, 2024)
The encounter between the concept of democracy and religious teachings, especially Islam, is interesting to discuss. This raises several relevant questions: Can democracy be considered within the framework of Islamic teachings? Are democratic values in line with Islamic teachings? Can Islamic principles be juxtaposed with democracy? In addition, what are the views of Islamic scholars, such as Abdul Karim Soroush, on the issue of democracy? Through a literature review, we can find some unique thoughts from Abdul Karim Soroush that are interesting to listen to. One of them is his concept of religious democracy, which also tries to redefine the meaning of religion and the understanding of religion itself. According to Soroush, democracy is currently an established idea. He also argues that democracy is not a monolithic concept, and neither is Islam. Although originating from Western culture, democracy can adapt to local conditions when it interacts with the local cultural context. Therefore, Soroush emphasized that there is no need to be afraid of democracy.